Factors associated with depression anxiety and stress in the context of covid-19 pandemic in police officers of metropolitan lima, Peru: Factores asociados a depresión, ansiedad y estrés en el contexto de la pandemia por covid-19 en policías de lima metropolitana, Perú - Apaza Llantoy, Katherine D. (2021)
Objective: To determine the factors associated with the development of depression, anxiety and stress in the context of the COVID-19 pandemic in police officers in Lima, Peru. Methods: Analytical cross-sectional study conducted in 210 police officers who were administered the Depression Anxiety and Stress Scale-21 (DASS-21) in October 2020, as well as a form, via Google Forms, to obtain sociodemographic and clinical data. A bivariate and a multivariate analysis were performed using crude and adjusted prevalence ratios, with a confidence interval >95% and a significance level of p≤0.05. Results: Depression, anxiety and stress prevalence rates were 11.43%, 10% and 7.62%, respectively. In the bivariate analysis, anxiety was associated with the number of children (cPR:3.18; 95% CI [1.10-9.17]; p:0.032) and history of disease (cPR:2.50; 95%CI[1.08-5.75]; p:0.031). For depression and stress, no significantly associated factors were found. In the multivariate analysis, an association between depression and age (aPR:2.50; 95%CI[1.02-6.10]; p:0.044) was found, as well as an association between stress and emotional situation (aPR:3.10; 95%CI[1.08-8.95]; p:0.034), COVID-19 diagnosis (aPR:3.18; 95%CI[1.02-9.92]; p:0.045) and history of disease (aPR:4.19; 95%CI[1.22-14.36]; p:0.022). Conclusions: A low prevalence of depression, anxiety and stress was observed in the study population. In addition, according to the multivariate analysis, the risk factors for stress were being single, having been diagnosed with COVID-19 and having a history of disease, while being 40 years old or younger was a risk factor for depression.